A geometrical optimization and comparison study on the charging and discharging performance of shell-and-tube thermal energy storage systems. (July 2022) - Mohaghegh, Mohammad Reza; Tasnim, Syeda Humaira; Mahmud, Shohel
Abstract: Shell-and-tube latent heat thermal energy storage (ST-LHTES) systems have been extensively studied due to their high thermal/cold storage capacity during the charging/discharging process and their wide range of applications. The thermal performance of these systems is heavily dependent on the shape and geometry of the shell part. This research aims to investigate the transient heat transfer of phase change material (PCM) in the vertical ST-LHTES systems during charging (melting) and discharging (solidification) and the impact of geometric design on the heat transfer characteristics and consequently the thermal performance of the system in both processes. For this purpose, phase change heat transfer in a conventional cylindrical shell is compared with conical configurations with arbitrary inclination angles. The different heat transfer characteristics, e.g., the rate of phase change fraction and the energy stored/released, are determined and compared for all systems to evaluate their thermal performance and find the optimal design. The phase change process is also numerically visualized to track the phase change interface during both charging and discharging processes. A dynamic adaptive mesh refinement technique is implemented to capture gradients and simulate phase change front accurately. Depending upon the inclination angle, a favorable result can be achieved for the charging process in conical shape compared with a cylindrical geometry, while inverse results are obtained for the discharging process. In other words, increasing the lateral slope of the shell from a vertical to tilted state enhances the melting process resulting in a faster energy storage rate during the charging process, whereas decreasing this slope leads to better thermal performance for discharging process. The optimum designs can improve the system performance by 52% and 56% for the charging and discharging processes, respectively. A comprehensive experimental setup is developed for the cylindrical case to visualize and compare the charging and discharging process experimentally as well. Results obtained from numerical simulations exhibit similar patterns to experimental visualizations. Highlights: Numerical and experimental investigation of charging and discharging processes inside ST-LHTES systems Comparison of geometric designs, i.e., cylindrical and conical shells on the performance of the system and optimization Investigating the effect of the shell inclination angle on charging and discharging powers Implementing the DAMR method to capture phase change front accurately and to reduce the computational costs Improving the system performance by 52% and 56% for the charging and discharging processes, respectively